Mapping Rural Local Government Capacity for Climate Resilience Projects in the United States - Smith, Kristin K.; Goto, Erica A.; Domingue, Simone J.; Kalafatis, Scott E.; Bartley, Meridith L.; Preston, Tara L.; Hernandez, Patricia G. (Public administration review, 2025)
Local government capacity gaps are primary barriers to implementing climate adaptation and disaster resilience projects. While over 85% of US municipalities have fewer than 10,000 people, the extent to which capacity restricts adaptation in rural governments is not understood. This research addresses that gap by developing a national Rural Capacity Index using indicators that highlight challenges disproportionately faced by rural places. When results are mapped, the Midwest stands out for lacking capacity at the county, county subdivision, and community scales. The index is then shown to have a positive relationship with success in securing competitive federal grants. There is an estimated 4% increase in the amount of funding awarded for every 1% increase in the index's percentile rank. The Rural Capacity Index provides scholars, practitioners, and policymakers a practical tool to identify and respond to disparities in local government capacity that constrain rural disaster resilience efforts.